IMPLEMENTASI POLITEKNIK DAN FUNGSINYA DALAM MEMPERSIAPKAN KEMAMPUAN-KEMAMPUAN YANG ADAPTABLE TERHADAP RAGAM TUNTUTAN DUNIA KERJA - Sukirno, - (1997)
This dissertation is the report of a research on the implementation of the D III Polytechnic, ITB, Mechanical Engineering Program. Preparation of adaptable abilities has been a major concern in the investment of human resources, particularly in relation to the 21st century, dealing with fast changing technology and demography of labor market. The study was aimed at finding out the ways ITB Polytechnic preparing adaptable competencies in the framework of curriculum implementation. The results of this study are expected to make conceptual and practical contributions to the improvement of Polytechnic curriculum and its implementation in Indonesia.The research focus was centered on the Polytechnic efforts in preparing abilities that be based on the cognitive skills. This focus covered three levels of study, i.e. the curriculum implementation at the institutional level, classroom level, and adaptability of graduates' capabilities as learning outcomes. The institutjion-level implementation put take with institutional activities to get the implementation closer to the ideas of curriculum design, whereas the classroom-level implementation focused on learning activities to indicate the efforts made to develop adaptable abilities. Finally, adaptability of abilities was related to the efforts the graduates made to adapt their learning outcomes to the working requirements.The naturalistic qualitative approach was applied. Data on the implementation at institutional and classroom levels were collected in the ITB Polytechnic context, while data on the adaptability of graduates' capabilities were collected in the industrial context. Data was collected through direct observation, interview, and documentary study. Data analysis was conducted in two phases; the first phase was done while collecting data at each respective site and the second one was done for the purpose of cross-site analysis. The data analysis was conducted through developing categories, analyzing relationships, formulating basic ideas, and making conclusions based on the concepts of curriculum implementation and adaptable abilities.